Applying the Delphi method to determine best practices for outsourcing logistics in disaster relief. Issue 3 (10th December 2019) - Gossler, Timo; Falagara Sigala, Ioanna; Wakolbinger, Tina; Buber, Renate
Abstract : Purpose: The purpose of this paper is to determine best practices of aid agencies for outsourcing logistics to commercial logistics service providers (LSPs) in disaster relief. Moreover, it evaluates the application of the Delphi method for research in humanitarian logistics. Design/methodology/approach: The paper is based on a two-round Delphi study with 31 experts from aid agencies and a complementary full-day focus group with 12 experts from aid agencies and LSPs. Findings: The study revealed 12 best practices for outsourcing logistics in disaster relief and a compilation of more than 100 activities for putting these practices into action. Experts consider a proper balance between efficiency and compliance, a detailed contract and a detailed service request most important. Additionally, the Delphi method was found to be a promising technique for research on humanitarian logistics. Research limitations/implications: By critically examining the Delphi method, this study establishes the basis for a wider application of the technique in the field of humanitarian logistics. Furthermore, it can help to prioritize future research as the ranking of practices reflects the priorities of practitioners. Practical implications: The paper provides guidance to practitioners at aid agencies in charge of outsourcing logistics. Originality/value: This research is one of the first in the field of humanitarian logistics to apply the Delphi method. Moreover, it addresses the lack of literature dealing with approaches for building successful cross-sectoral partnerships.